The acceptability and tolerability of nasal douching in children with allergic rhinitis: A systematic review. (July 2017) - Gutiérrez-Cardona, Nelson; Sands, Paula; Roberts, Graham; Lucas, Jane S.; Walker, Woolf; Salib, Rami; Burgess, Andrea; Ismail-Koch, Hasnaa
Abstract: Background: Allergic rhinitis (AR) is a significant issue in children. Treatment options include allergen avoidance, pharmacotherapy and immunotherapy. The use of nasal saline douching (NSD) in children has recently gained acceptability. However, there is limited data regarding the acceptability and tolerability of NSD in children with AR. Methods: A search was conducted using Medline and Embase databases from January 1946 until June 2015 on the use of NSD in children aged 4–12 years with AR. All publications identified that assessed the beneficial effects, acceptability and tolerability were included. Results: 40 studies were analyzed. Data varied considerably in terms of saline solutions used, modality of application, participant numbers, study design, follow up and outcomes. Factors that appear to influence the acceptability and tolerability of NSD include parental and health professionals' preconceptions, and characteristics of the solution. Conclusions: Nasal saline douching appears to be effective, being accepted and tolerated in the majority of children (78–100%). NSD has a significant positive impact on the quality of life in children with allergic rhinitis. When used as an adjunctive treatment having mainly a cleansing property, NSD potentiates the effects and may reduce the dose required of AR medications. Among the principal factors that influence the acceptability and tolerability of NSD are the child's age, delivery system and method, and tonicity. Nasal saline douching provides an accessible, low cost, low morbidity, easy to use treatment in children with allergic rhinitis.